Menyikapi Keberadaan Aliran Sempalan - ABDURRAHMAN MASUD (Jurnal Dialog, 2017)
This article discusses the differences in religious interpretation of the scripture and the emergence of various religious beliefs, understanding and sects. Inspite of these differences, most of the religious sects follow the main pillars of their religious teachings and subject to the majority group. Nevertheless, many others tend to pull out from this mainstream group and build another different religious orientation. These so-called splinter groups sometimes oppose againts the teachings developed by the mainstream group. In Islam, as argued by this article, the differences in religious orientations have resulted various reactions and treatments from the rest of the Muslims. The form of the reactions partly relies on the level of the Muslims’ educational background. The higher the level of education, the more tolerant the Muslims’s attitude toward the religious differences will be.